A Note on Variations in the Terms of Trade and a General Dollar Problem - Zupnick, Elliot (The Review of Economics and Statistics, 1956)
reserves, which was compounded by the Christmas seasonal pressures upon bank reserve positions, including an unexpected high volume of dividend payments and tax disbursements. The lesson to be drawn from this experience seems clear. A flexible monetary policy,4 about which the present Reserve Board has exuded so much pride, requires flexible monetary instruments rather than a dogmatic subservience to a single rigid mechanism for implementing credit objectives. Dealing in all market sectors, as the occasion warrants, can alone serve central banking ends. Confinement to the bills sector will inevitably create a Hobson's choice of acknowledging doctrinal inconsistency or policy impotency in a situation such as that which developed in early December I955.